The theory of bonds II: Closed 6R linkages with maximal genus. (May 2015) - Hegedüs, Gábor; Li, Zijia; Schicho, Josef; Schröcker, Hans-Peter
Abstract: In this paper, we study closed linkages with six rotational joints that allow a one-dimensional set of motions. We prove that the genus of the configuration curve of such a linkage is at most five, and give a complete classification of the linkages with a configuration curve of genus four or five. The classification contains new families.